2017
DOI: 10.3390/nu9101053
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbial Metabolite Trimethylamine-N-Oxide Is Present in Human Cerebrospinal Fluid

Abstract: Trimethylamine-N-oxide (TMAO) is a small organic molecule, derived from the intestinal and hepatic metabolism of dietary choline and carnitine. Although the involvement of TMAO in the framework of many chronic diseases has been recently described, no evidence on its putative role in the central nervous system has been provided. The aim of this study was to evaluate whether TMAO is present at detectable levels in human cerebrospinal fluid (CSF). CSF was collected for diagnostic purposes from 58 subjects by lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 16 publications
0
89
0
Order By: Relevance
“…In a murine cohort, serum TMAO was connected to the process of brain aging (Li et al, 2018[ 8 ]). Recently, it was shown that TMAO is also present in the human cerebrospinal fluid (CSF) (Del Rio et al, 2017[ 4 ]). Individuals with Alzheimer's disease were observed with elevated CSF TMAO concentrations (Vogt et al, 2018[ 21 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In a murine cohort, serum TMAO was connected to the process of brain aging (Li et al, 2018[ 8 ]). Recently, it was shown that TMAO is also present in the human cerebrospinal fluid (CSF) (Del Rio et al, 2017[ 4 ]). Individuals with Alzheimer's disease were observed with elevated CSF TMAO concentrations (Vogt et al, 2018[ 21 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical penetration of TMAO across the BBB was unknown at the time of the study, and 26% of the TMAO penetrated the NVU. 119 The significance of this study was that TMAO's penetration of the BBB was subsequently confirmed clinically by the analysis of spinal-tap fluid from > 50 patients, 129 constituting what is believed to be the first MPS prediction later confirmed in humans.…”
Section: Oocs For In Vitro Studies Of Microbiome-organ-organ Interactmentioning
confidence: 76%
“…It was shown that TMANO lowers the critical concentration of tubulin needed for tubulin assembly by modulating binding of protein kinase A-phosphorylated microtubule-associated protein tau to form tubulin. It seems that TMANO levels are not related to neurological disorders [76]. However, since one hallmark of AD is hyper-phosphorylation of the microtubule-associated protein Tau, this finding offers a therapeutic implication for TMANO in Alzheimer disease.…”
Section: Microorganisms Found In Alzheimer Diseasementioning
confidence: 98%